The use of interactive and diagnostic control systems in the management of an undergraduate course - Dal Magro Dal Magro, Cristian; Dagostim Picolo, Jaime; Facin Lavarda, Carlos Eduardo (Cuadernos de Administración, 2017)
Due to the complexity in defining the use of information systems in an interactive and/or diagnostic manner, this study aims at verifying which management control systems may be used in an interactive and diagnostic form in an administration course of a higher education institution located in Santa Catarina, Brazil. As for the research method, it was carried out over three stages: individual in-depth interviewing, documentary research and the applying of a questionnaire to the advisory board of the course: Structuring Faculty Core - SFC. The results indicate that the systems “generation of ideas” and “project management” should be implemented at least as a diagnostic systems. For the systems “faculty performance management”, “scientific research management” and “academics’ performance in disciplines”, interactive implementation is recommended. The systems of “budgeting” and “academic system” do not generate significant rejection if not present and they do not add value if present. Finally, the systems “academics’ performance in the Integrated Mock Test on Managerial Knowledge” and “course extension performance” add value if put in practice; however, if implementing them is not possible, it does not generate significant rejection. The contributions of this study concern defining a methodology to support organizations in defining the configuration of information systems, whether interactive or diagnostic, aimed at optimizing the costs of implementing information systems, but also at verifying the opinion of a group of people who participate in the administration of the institution and contribute to the legitimacy of decisions.